2014
DOI: 10.1021/ol5020015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silyl Monoperoxyketals by Regioselective Cobalt-Catalyzed Peroxidation of Silyl Enol Ethers: Application to the Synthesis of 1,2-Dioxolanes

Abstract: The cobalt-catalyzed peroxidation of silyl enol ethers with molecular oxygen and triethylsilane provided silyl monoperoxyketals in 54%-96% yield. These compounds serve as precursors to peroxycarbenium ions, which undergo annulations to provide 1,2-dioxolanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“… 38 Treatment of these compounds with 5 mol % of SnCl 4 and alkene 29 , 30 , 38 , or 40 followed by immediate deprotection yielded FINO 2 ( 4 ) and derivatives 31 − 33 , 37 , 39 , and 41 . 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 Treatment of these compounds with 5 mol % of SnCl 4 and alkene 29 , 30 , 38 , or 40 followed by immediate deprotection yielded FINO 2 ( 4 ) and derivatives 31 − 33 , 37 , 39 , and 41 . 38 …”
Section: Resultsmentioning
confidence: 99%
“…Treatment with LiN i Pr 2 yielded silyl enol ethers 23 − 25 and 35 . 38 Regioselective cobalt-catalyzed peroxidation of these products furnished mixed peroxyketals 26 − 28 and 36 . 38 Treatment of these compounds with 5 mol % of SnCl 4 and alkene 29 , 30 , 38 , or 40 followed by immediate deprotection yielded FINO 2 ( 4 ) and derivatives 31 − 33 , 37 , 39 , and 41 .…”
Section: Resultsmentioning
confidence: 99%
“…144 For example, hydrosilylperoxidation of silyl enol ether 18 gives peroxy compound 19 , and treatment of 19 with catalytic SnCl 4 at −78 °C in the presence of an alkene provides 1,2-dioxolane 20. Woerpel has also made 1,2-dioxepane rings.…”
Section: C-o Bondsmentioning
confidence: 99%
“…Woerpel et al expanded the scope of this reaction to include silyl enol ethers. 23 Initial studies indicated that peroxidation of triethylsilyl enols ethers, rather than the more labile trimethyl silyl equivalents, resulted in fewer decomposition products, easier purication and higher yields. Further optimisation revealed that a combination of Co(thd) 2 in triuorotoluene led to an additional increase in yield.…”
Section: Isayama-mukaiyama Reactionmentioning
confidence: 99%